Sustainable Supply Chain Finances implementation model and Artificial Intelligence for innovative omnichannel logistics - Pawlicka, Kinga; Bal, Monika (Zielona Góra: Faculty of Economics and Management Press)
Whilst there is significant research on supply chain finance, there is little information about its application to the omnichannel logistics. Hence, the primary adopted goal is to identify the ways of supporting the implementation and development of SSCM with use of Artificial Intelligence and developed SSCF implementation model.
Keywords: sustainable finance; supply chain management; artificial intelligence; omnichannel; zrównoważone finanse; zarządzanie łańcuchem dostaw; sztuczna inteligencja; innowacyjna logistyka